Bread with Pennisetum glaucum (L. R. Br.) seed flour: food product development - Silva, Gabriela de Souza; Cintra, Patrícia; Massulo, Andreia de Oliveira; da Silva, Lucas de Melo (Seven Editora, 2023)
This is an experimental, descriptive, and cross observational research that reported the formulation of bread with flour of Pennisetum glaucum (L. R. BR.) in concentrations (10, 20 and 50%) in replacement of white wheat flour. In this study, the technical sheet of preparation and nutritional information of the product was made. The formulation with 20% millet stood out in the sensorial analysis with a harmonic and attractive flavor, with a 95% yield, a cost of R$ 12,41 and a total weight of 826g. The development of this product verified the possibility of using millet flour for the production of food products with nutritional characteristics and low cost for preparation. The insertion of millet in human nutrition is of great interest because besides being a whole grain, it is gluten-free and rich in nutrients. DOI: https://doi.org/10.56238/colleinternhealthscienv1-034